Кинетика выпечки бисквитного полуфабриката - Дорохович, Антонелла Николаевна; Бондаренко, Евгения Григорьевна (My University, 1972)
Статья посвящена исследованию процесса выпечки бисквитного полуфабриката. Приведены и исследованы температурные кривые прогрева и кривые роста бисквитного полуфабриката при выпечке. The article deals with the process of semi-finished biscuit baking. Are investigated and temperature curves of heating and the growth curves of semi-finished biscuit baking.
Keywords: кинетика; бисквитный полуфабрикат; гигротермическая обработка; температура; кривые роста; кафедра технології хлібопекарських і кондитерських виробів; kinetics; sponge cake mix; processing of gigrotermik; temperature; growth curves